DAMPAK DAN PENYEBAB VARIATION ORDER (VO) PADA PROYEK APARTEMEN ICON - GRESIK - Felicia Tria Nuciferani S.Pd., M.T.; Siti Choiriyah; Feri Harianto; Fajar D.Y .Jatmiko (Institut Teknologi Adhi Tama Surabaya, 2023)
The Construction of Icon Apartment Project are construction projects that have different cause variation orders. This research aims to determine the percentage of VO (Variation Order), the highest factor of VO, and the impact of VO. Data collection used questionnaires accompanied by an interview process with the project manager for each project. Data processing techniques use validity test, reliability test, and mean test. The results obtained in this study are the percentage of VO for the Caspian project 13.50% and the Icon project 11.30%. The highest VO factor for the Caspian project was extreme weather 4.80 and the Icon apartment was a design change of 4.6. The emergence of VO has an impact on the addition of costs and work schedules for each project.